The Method of Images Revisited: Approximate Solutions in Wedge‐Shaped Aquifers of Arbitrary Angle - I. A. Nikoletos; K. L. Katsifarakis (Water Resources Research)
Abstract This paper focuses on deriving new approximate analytical solutions in wedge‐shaped aquifers. The proposed methodology is applicable to any type of aquifer namely, leaky, confined and unconfined, under both steady state and transient flow conditions. By applying the method of images and separating the flow field into sections using physical arguments, approximate analytical expressions are obtained for the drawdown function, which in contrast to the conventional theory, are applicable to any arbitrary wedge angle. Moreover, the solutions fully observe the boundary conditions, while they preserve the continuity of the drawdown, which can be calculated directly at any point of the flow field. Nevertheless, comparison of the results of the new approximate analytical solutions to numerical ones, has been considered necessary to check their validity. MODFLOW, a well‐known numerical tool is used to calculate the numerical results. The discrepancies between the numerical results and those of the approximate analytical solution are negligible. The main advantages of the proposed methodology are the following: (a) The model needs only finite number of terms compared to conventional analytical and numerical solutions that involve infinite series, (b) The computational load is low, so it can be easily used in conjunction with meta‐heuristic algorithms to solve groundwater resources optimization problems, (c) Stream depletion rate can be calculated rather accurately and (d) The method is applicable to related flow problems.